Pengaruh Pengetahuan (Knowledge), Keyakinan (Confidence), Keterampilan (Skill) dan Religiusitas Intrinsik tentang Perbankan Syariah terhadap Keputusan Pengambilan Kredit - Asep Kurniawan; Yuri Haspari; Icih Icih (Jurnal Akuntansi dan Governance Andalas, 2018)
This study aims to examine the effect knowledge of syariah banking products and services, confidence, skills, intrinsic religiosity of syariah banking on taking of credits. The population in this study were 150 respondents from the Bank Syariah Mandiri customers. The sampling technique was carried out using non probability sampling. Data collection techniques in the form of questionnaires, Observation, and Library Research. The method used is quantitative. The analytical tool used in this research is logistic regression and hypothesis significant individual parameters test (test wald), significant simultaneous test (Omnibus of model coefficients), test coefficient determinasi (Cox dan Snell’s R Square dan Nagelkerke R Square). The results of this study indicate that a variable knowledge of positive and significant effect against the decision in taking credit, confidence of positive and significant effect against the decision in taking credit, skills have no effect signifikan effect against the decision in taking credit,while intrinsic religiosity significant effect against the decision in taking credit.